Go digital: can the money-gift function promote the use of e-wallet apps? - Lim, Xin Jean; Ngew, Phillip; Cheah, Jun Hwa; Cham, Tat Huei; Liu, Yide (Emerald Publishing, 2022)
Purpose: One of the impacts of the COVID-19 pandemic is that using an e-wallet – a contactless process – rather than a payment terminal is an intuitively safer option. This study is grounded in cognitive absorption theory and investigates how the use of the money-gift function influences the intention to continue using an e-wallet app. Design/methodology/approach: Using a cross-sectional approach, a structured questionnaire was designed and distributed to the target respondents in Malaysia through social media platforms. The data were collected with purposive sampling and a total of 350 eligible responses were analyzed with partial least square structural equation modeling (PLS-SEM). Findings: Cognitive absorption significantly influenced the perceptions of e-wallet apps (perceived ease of use and perceived usefulness). The intention to continue using an e-wallet app was positively predicted by attitude and subjective well-being. Furthermore, this study found that the path between attitude and the intention to continue use was mediated by subjective well-being, whereas perceived security moderated the path between cognitive absorption and perceptions of an e-wallet app. Practical implications: The results offer much-needed broad guidance for e-wallet service providers. In particular, the findings reveal how implementing money-gift functions promotes various positive outcomes that influence the intention to continue using an e-wallet app. Originality/value: Previous research on e-wallets considered only the basic characteristics of an e-wallet app when studying continuous usage. Few studies have empirically examined the innovative function of money gifts. Therefore, this study is among the first to offer empirical insights into how immersion and cognitive interaction with the money-gift function can influence user perceptions and behavior toward e-wallet apps.